Budaya kesukarelawanan dan keunikan etnografi dapur jalanan Kuala Lumpur / Syafiq Sham ...[et al.] - Sham, Syafiq; Selvaratnam, Doris Padmini; Jasni, Haziq Fikri; Harun, El Hanis (Universiti Teknologi MARA, 2021)
Volunteering culture is crucial in shaping the nation's unity in navigating the global setting, especially in a country with multiple ethnicity, culture and religion such as Malaysia. The objective of this study is to understand the volunteering culture practiced by Dapur Jalanan Kuala Lumpur (DJKL) and its ethnography. The data is obtained through the ethnography approach as a participant and observer, together with a set of questionnaires distributed to 295 volunteers affiliated with DJKL. Aside from that, an interview is conducted with a few of DJKL's full-time volunteers and homeless people located at Jalan Panggong. Based on the statistics, a majority of DJKL's volunteers consisted of young women. Besides, DJKL accepts first-timer volunteers for the volunteering programs run by nongovernmental organizations (NGO) at the rate of 69 percent, while the remaining 93 percent are volunteers who are not affiliated with any of the established NGOs. The ethnography pattern shows that DJKL practices volunteering activities with an emphasis on environment, ethics, arts and culture. This study suggests an establishment of a 'volunteer pool' to increase the participation of full-time volunteers and collaborate with university students' societies to enhance the volunteering culture. On the final note, a statistic unit for DJKL should be established to allow a more consistent and systematic data management to take place in the organization.